2020
DOI: 10.5114/aoms.2020.97285
|View full text |Cite
|
Sign up to set email alerts
|

A study on health and the association between overweight/obesity and otorhinolaryngological diseases in 6- to 17-year-old children from Wrocław, Poland

Abstract: Introduction: Childhood overweight and obesity have become a global problem in the past three decades. There are very few studies which examine the correlation between body mass index (BMI) and the development of otorhinolaryngological diseases in children. The objective of the study was to determine the association between overweight or obesity in children and the occurrence of otorhinolaryngological diseases. Material and methods: The survey study was based on a parent-reported multidisciplinary questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Nonetheless, the pathophysiological mechanisms linking allergy and ATH remain uncertain. Although studies suggested chronic in ammation in local adeno-tonsillar tissue is characterized in children with obesity and ATH [4,7,16], the direct role of obesity has not been elucidated which may interact with both allergy and ATH [5,6,10]. We found that leptin and L/A ratio were signi cantly higher in children with ATH, and atopic children were characterized by increased leptin level and L/A ratio and decreased adiponectin level.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Nonetheless, the pathophysiological mechanisms linking allergy and ATH remain uncertain. Although studies suggested chronic in ammation in local adeno-tonsillar tissue is characterized in children with obesity and ATH [4,7,16], the direct role of obesity has not been elucidated which may interact with both allergy and ATH [5,6,10]. We found that leptin and L/A ratio were signi cantly higher in children with ATH, and atopic children were characterized by increased leptin level and L/A ratio and decreased adiponectin level.…”
Section: Discussionmentioning
confidence: 66%
“…Obesity in childhood is considered to be related to increased risk of otorhinolaryngological diseases [5]. Recent studies have discovered that children with obesity have a higher prevalence of ATH compared to peers with normal weight [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 This is consistent with the previous studies that have suggested a possible association between obesity and adenotonsillar hypertrophy. 6,7 Adipose tissue deposited around the pharynx and neck, along with hypertrophic adenoids largely plays a part in obstructive sleep apnea(OSA) in obese children. 7,[15][16][17] Therefore, obese or overweight AH children are more likely to have symptoms such as snoring and openmouth breathing getting their parents' attention to accepting further treatment in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…4 The global prevalence of obesity has tripled over the past decade, both in adults and children. 5,6 Previous studies 6,7 have suggested a possible relationship between adenotonsillar hypertrophy and obesity rates. Nevertheless, considering the small sample size, the correlation between obesity and adenoid hypertrophy is worthy of further study.…”
Section: Introductionmentioning
confidence: 99%